Functional genomics indicates yeast requires Golgi/ER transport, chromatin remodeling, and DNA repair for low dose DMSO tolerance - Gaytán, Brandon D.; Loguinov, Alex V.; De La Rosa, Vanessa Y.; Lerot, Jan-Michael; Vulpe, Chris D. (Frontiers in Genetics, 2013)
Dimethyl sulfoxide (DMSO) is frequently utilized as a solvent in toxicological and pharmaceutical investigations. It is therefore important to establish the cellular and molecular targets of DMSO in order to differentiate its intrinsic effects from those elicited by a compound of interest. We performed a genome-wide functional screen in Saccharomyces cerevisiae to identify deletion mutants exhibiting sensitivity to 1% DMSO, a concentration standard to yeast chemical profiling studies. We report that mutants defective in Golgi/ER transport are sensitive to DMSO, including those lacking components of the conserved oligomeric Golgi (COG) complex. Moreover, strains deleted for members of the SWR1 histone exchange complex are hypersensitive to DMSO, with additional chromatin remodeling mutants displaying a range of growth defects. We also identify DNA repair genes important for DMSO tolerance. Finally, we demonstrate that overexpression of histone H2A.Z, which replaces chromatin-associated histone H2A in a SWR1-catalyzed reaction, confers resistance to DMSO. Many yeast genes described in this study have homologs in more complex organisms, and the data provided is applicable to future investigations into the cellular and molecular mechanisms of DMSO toxicity.